Assessing the potential of highly permeable reverse osmosis membranes for desalination: specific energy and footprint analysis - Lim, Yu Jie (2022)
The ultra-permeable membranes (UPMs) are expected to reduce the specific energy consumption (SEC) of desalination, but the potential of UPMs in hollow fiber configuration has not been well quantified. Herein, we analyse the SEC and footprints of UPM modules in three feed salinities: seawater reverse osmosis (SWRO), brackish water RO (BWRO) and low-pressure RO (LPRO). Through the modelling the fluid dynamics and mass transport of RO systems, we find that a tripling in spiral-wound SWRO membrane permeability (based on the current value of 1 L m−2 h−1 bar−1; LMH/bar) could result in 16% decrease in SEC. Contrastingly, the quadrupling of hollow fiber SWRO membrane permeability (based on the current value of 0.25 LMH/bar) could reduce the SEC by 23%. According to our analysis, hollow fiber and spiral-wound SWRO membranes with permeabilities up to 1 LMH/bar and 3 LMH/bar, respectively, can reduce the SEC of seawater desalination. On the other hand, membranes with permeabilities up to 9 LMH/bar and 12 LMH/bar can lead to SEC savings in BWRO and LPRO desalination, respectively. This study provides a general guidance to RO membrane researchers on the permeability upper-limit of which UPMs could bring about SEC and footprint savings at a system level.